Major trends in research themes from AERC proceedings (1990-2001) - Craig A. Campbell; Christophe Cheroret (Adult Education Research Conference, 2019)
The roundtable will focus on a critical literature review research approach and preliminary trend findings from a document analysis of the research themes from AERC proceedings from 1990 to 2001.
Keywords: adult and continuing education history; critical literature review; AERC proceedings